MARKETING AND QUALITY OF PENCAK SILAT SCHOOL SERVICES - Nugroho, Agung (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2010)
In accordance with the development of the era, each Pencak Silat (kind of martial arts) school requires to rethink the objectives and strategy in marketing ofPencak Silat. This is based on rapid changes in technologY; economic, social and cultural rights so that they can follow in accordance with the development and the needs of the community. This rapidly changes can make the privilege principles in carry on business in the past that no longer apply.The challenge in the recent years, there are many Pencak Silat school face the new problem, they have to fight in a harder globalization competition, for example: the coaching qualities, neglected infrastructure improvement, achievement stagnation, and inability educator. Those are the problem but can be a business opportunity for Pencak Silat School in the marketing process.Sport activity which involved the facilities called goods and the activity of the coaches called service. Both of the goods products and services cannot be separate in the process of teachinglearning, so, the service quality of Pencak Silat must give many attentions so that it will improve the service quality. Keywords: marketing, service quality; pencak silat